Autonomous racing using Linear Parameter Varying-Model Predictive Control (LPV-MPC). (February 2020) - Alcalá, Eugenio; Puig, Vicenç; Quevedo, Joseba; Rosolia, Ugo
Abstract: This article presents an innovative control approach for autonomous racing vehicles. Linear Parameter Varying (LPV) theory is used to model the dynamics of the vehicle and implement an LPV-Model Predictive Controller (LPV-MPC) that can be computed online with reduced computational cost. The optimal time problem is solved by an optimal off-line trajectory planner that calculates the best trajectory under the constraints of the circuit. An identification of the system model based on optimization is also carried out. The planning and control scheme is validated in simulation and experimentally in a real platform where the effectiveness of the proposed LPV-MPC is demonstrated.